FREQUENCY OF MIGRAINE-RELATED DEPRESSION AMONG MIGRAINEURS IN PAKISTAN: A CROSS-SECTIONAL STUDY - AZHAR, A; IRFAN, F; SHAKOOR, H; KHUDA, IE (Biological and Clinical Sciences Research Journal, 2024)
Depressive disorders are among the leading causes of disability globally and can further complicate the clinical manifestation if coupled with other comorbidities. Objective: The main objective of the study is to find the frequency of migraine-related depression among migraineurs in Pakistan. Methods: This cross-sectional study was conducted at Fauji Foundation Hospital Rawalpindi from January 2024 to June 2024. Data were collected from 240 patients. Data were collected through a designed questionnaire which contain all data related to depression and awareness of patients. All the data related to sociodemographic factors, history, disease duration, and frequency of migraine attacks were noted. Results: Data were collected from 240 participants with a mean age of 35.4±9.8 years. Most patients (60%) fall in the 30-45 age range. Regarding the duration of migraines, 45.8% of patients had suffered for 1-5 years, while 41.7% had migraines for more than 5 years. The majority of participants (41.7%) experienced 3-4 migraine attacks per month. Regarding pain severity, half of the patients (50%) reported moderate pain, while 33.3% experienced severe pain. The results showed that 66.7% of migraine patients experienced some level of depression, as measured by the PHQ-9 scale. Conclusion: It is concluded that depression is highly prevalent among migraine sufferers in Pakistan, with more than two-thirds of patients experiencing some form of depressive symptoms. The severity of depression is significantly associated with migraine frequency, duration, and pain intensity.